To the chiefs and principal men in the Islands of the Marquesas in the South Seas - New South Wales; Macquarie, Lachlan; State Records Authority of New South Wales; Adam Matthew Digital (Adam Matthew Digital, 1816)
Letter from the Governor of New South Wales to the chiefs of the Marquesas regarding the cruelty to the indigenous people by John Martin, master of the Queen Charlotte, 1816